A case report of CRB2 mutation identified in a Chinese boy with focal segmental glomerulosclerosis. Issue 37 (September 2018) - Fan, Jiaojiao; Fu, Rong; Ren, Fuxian; He, Junjie; Wang, Shujing; Gou, Mengfan
Abstract: Rationale: Focal segmental glomerulosclerosis (FSGS) is a common disease resulting in end-stage renal disease. The incidence of FSGS is increasing in Western countries. The clinical manifestations include proteinuria, hypoproteinemia, oedema, and hypertension. Single-gene heritable mutations are considered to be the source of FSGS pathogenicity according to recent in-depth studies on the pathogenesis. Here, we first reported the case of a Chinese boy whose histology presented with FSGS caused by a compound heterozygous mutation. Patient concerns: A 7-year-old Chinese boy was repeatedly admitted to our hospital for fever, cough, and proteinuria since he was 1.6 years old. Diagnoses: FSGS was identified by renal biopsy. Whole exome sequencing (WES) showed that a novel mutation of crumbs homolog 2 (CRB2) was identified in a Chinese boy with FSGS. Interventions: Patient was treated with low-dose corticosteroid and mycophenolate mofetil for maintenance therapy. Outcomes: At last follow-up, protein (+∼++) was observed in his urinalysis. Lessons: We identified a novel mutation of CRB2 in a Chinese boy with FSGS that had never been described in a previous report. These findings suggested that mutations in recessive disease genes are more frequent among early-onset disease.